The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00784-006-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of chemomechanical and mechanical caries removal: status of the restorations at 3, 6, 9 and 12 months

Abstract: In this study, the clinical efficacy of Carisolvtrade mark system and the hand excavation method in the removal of occlusal dentine caries of primary molar teeth was evaluated. Both Carisolv system and hand excavation method were applied for the removal of caries on different teeth of the same children. After the removal of the caries, Dyract AP materials were used to restore the teeth. The clinical follow-up was made every 3 months within a year. The clinical evaluations of restorations were carried out in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 27 publications
0
35
0
13
Order By: Relevance
“…8 Kirzioglu et al compared the chemomechanical and mechanical method of caries removal; at 3, 6, 9 and 12 months and showed that at the end of 1 year, in terms of marginal adaptation and secondary caries, there was no statistical significance which was in accordance to the present study. 9 After a period of 10 months secondary caries in teeth treated with papain gel was 21.6% and in conventional method it was 15.7%. The difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…8 Kirzioglu et al compared the chemomechanical and mechanical method of caries removal; at 3, 6, 9 and 12 months and showed that at the end of 1 year, in terms of marginal adaptation and secondary caries, there was no statistical significance which was in accordance to the present study. 9 After a period of 10 months secondary caries in teeth treated with papain gel was 21.6% and in conventional method it was 15.7%. The difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 98%
“…In two studies, Fure et al [9,13] found the majority of composite fillings placed in adult patients after the chemomechanical caries removal to be intact after one year (29 of 31, and 167 of 177, respectively). Kirzioglu et al [19] evaluated the status of compomer restorations in primary molars after the caries excavation with Carisolv and reported 27 of 28 teeth to be clinically excellent or acceptable at the end of the experimental period.…”
Section: Discussionmentioning
confidence: 98%
“…3,[5][6][7] Derin dentin çürüklerinin varlığında, pulpanın perforasyon riski göz önüne alınırsa, pulpanın vitalitesini koruyabilmek ve diĢin ağızda kalma süresini artı-rarak daha uzun süre fonksiyon görmesini sağlamak amacıyla daha konservatif bir yaklaĢım olan çürüğün selektif olarak uzaklaĢtırılması gündeme gelmiĢtir. 5,8 Bu amaçla geliĢtirilen selektif yaklaĢımlar, enfekte dentin, etkilenmiĢ dentin ve sağlıklı diĢ dokularının ayırt edilebilmesine yardımcı olarak, derin dentin çürüklerinde pulpaya zarar vermeden operatif iĢlemlerin tamamlanmasını sağlamaktadır. Selektif doku uzaklaĢtırıl-masında kullanılan yöntemler Ģunlardır: 1.Polimer Frezler: Elmas ve tungsten karbit frezler; enfekte dentin, etkilenmiĢ dentin ve sağlıklı doku ayrımı yapmadan, uygulandığı dokunun tamamını uzaklaĢtırmaktadır.…”
Section: çüRüğü Uzaklaģtırmada Selektif Yaklaģımlarunclassified
“…23 Günümüzde kullanılmakta olan enzim bazlı kemomekanik ajanlar ise; Papacarie (Formula and Acao, Sao Paulo, Brezilya) ve hala deneysel aĢamada olan Biosolv (SFC-V and SFC-VIII, 3M- Kemomekanik yöntemlerin çürüğün uzaklaĢtı-rılmasındaki etkinliği diğer yöntemlerle benzer olsa da dezavantaj olarak uygulama daha uzun sürmekte ve jelin uygulanacağı çürük alanına ulaĢmak veya en son kavite sınırlarını düzeltmek amacıyla frezlerin kullanılması gerekmektedir. 5,17,21,25,[30][31][32][33] 3.Çürük Boyaları: Çürük boyalarının kulanı-mının ilk kez 1970'lerde Fusayama tarafından kulanı-lan bazik fuksin ile gündeme geldiği bildirilmiĢtir. 34 Bazik fuksin, propilen glikol içerisinde %1 asit kırmızı ve povidon iyodür çürük boyası olarak kullanılmıĢtır ancak genotoksisite çalıĢmalarında bazik fuksinin ciddi mutajenik etkileri gözlenmiĢtir.…”
Section: çüRüğü Uzaklaģtırmada Selektif Yaklaģımlarunclassified